PWE-032 Endoscopic mucosal resection (EMR) followed by adjuvant radiofrequency ablation (RFA) can result in better outcomes compared to EMR alone in patients with Barrett's early neoplasia (EN). A comparative study from a tertiary centre in the UK. (28th May 2012) - Sami, S; Telakis, E; Mannath, J; Kaye, P; Ragunath, K
Abstract : Introduction: RFA has shown efficacy in eradicating Barrett's EN (high grade dysplasia (HGD) or intra-mucosal cancer (IMC)). To our knowledge, there are no studies directly comparing outcomes in patients with EN who undergo EMR alone vs EMR followed by RFA. The aim of this study was to assess the efficacy, safety and long term outcomes of adjuvant RFA in this setting. Methods: We searched our prospective Barrett's Oesophagus EMR database for patients who had EMR of lesions harbouring EN followed by RFA for eradication of residual Barrett's mucosa between 2007 and 2008 as part of a multi-centre trial (intervention group). The control group included patients with similar lesions who had undergone EMR followed by surveillance of residual Barrett's mucosa. The two groups were matched for any potential confounders to minimise bias. Results: There were 13 patients in each group. Mean age in the EMR group and EMR+RFA group was 70 and 59 years, respectively. Both groups were equally matched in terms of male to female ration (12:1); length of circumferential Barrett's mucosa; lesion Paris classification; mean lesion size; and resection type (Piecemeal or En-bloc). The mean duration of follow-up in the EMR group was 21 months compared to 32 months in the EMR+RFA group. The histological characteristics of lesions in both groups are shown in the table below (Abstract PWE-032 table.1 ). Overall, histological eradication of EN was achieved in eight (62%) patients in the EMR group and 13 (100%) in the EMR+RFA group at the last follow-up. Persistence or recurrence of EN and the need for further EMR during follow-up occurred in five patients (38%) in the EMR group (two of them had Oesophagectomy) compared to only one (8%) in the EMR+RFA group. One patient (8%) in the EMR group developed oesophageal stricture and no complications occurred in the other group. Conclusion: These data suggest that adjuvant RFA in this setting can have a significant positive impact on the long term success rate of histological eradication of EN in Barrett's Oesophagus as well as reducing the risk of recurrence of those lesions. It can reduce the need for subsequent EMRs and radical surgery with no safety concerns. The long duration of follow-up and control for confounders add significant validity to the results, despite the relatively small number of patients included. Competing interests: S Sami: None declared, E Telakis: None declared, J Mannath: None declared, P Kaye: None declared, K Ragunath Grant/Research Support from: Olympus, Cook and Barrx medical.